State Elimination Ordering Strategies: Some Experimental Results - Nelma Moreira (2010)
Recently, the problem of obtaining a short regular expression equivalent to a given finite automaton has been intensively investigated. Algorithms for converting finite automata to regular expressions have an exponential blow-up in the worst-case. To overcome this, simple heuristic methods have been proposed. In this paper we analyse some of the heuris- tics presented in the literature and propose new ones. We also present some experimental comparative results based on uniform random gener- ated deterministic finite automata.